What are the attractiveness aspects that influence customer loyalty to homestays? A study in Taiwan - Toh, Steven Teong-Jin; Tan, Cheng Ling; Yeo, Sook Fern (Penerbit Universiti Kebangsaan Malaysia, 2016)
The purpose of this study is to investigate the direct relationship between perceived attractiveness aspects and customer loyalty. The perceived attractiveness aspects are operationalized into five dimensions, namely surroundings of the building and features; service quality; homestay facilities; homestay operation and management; and homestay geist and community co-prosperity. The hypotheses are postulated and tested using a sample of 566respondents that were homestay customers in Taiwan The data used in this study was collected via self-administered questionnaires The study employs the structural equation modeling (SEM) technique to test the validity of the proposed hypotheses via Smart-PLS software. The results show that only four out of five sub-hypotheses are supported. The conclusion of this study provides theoretical implications and practical implications, as well as suggestions for future studies either in Malaysia or Taiwan.